Efficient shoot and root formation from cotton shoot apices - (:unkn) unknown (PLEIADES PUBLISHING INC, 2009)
Successful shoot and root induction were obtained from shoot apices of two cotton (Gossypium hirsutum L.) genotypes, Nazilli 84S and Cukurova 1518, which are widely planted in Turkey. Plant tissue culture systems were established on Murashige and Skoog (MS) medium supplemented with various plant growth regulators using seven-day-old shoot apices as explants. The shoot apex size was of 2-3 mm; it contained the meristem and unexpanded leaves. Shoot apices were placed on MS plus vitamins and combinations of various plant hormones. The best regeneration responses were obtained for cv. Nazilli 84S (98%) on MS + 0.1 mg/l kinetin (KIN) + 1 g/l polyvinylpyrrolidone (PVP) and for Cukurova 1518 (94%) on MS + 0.1 mg/l KIN + 2 mg/l NAA + 1 g/l PVP. Including germination, all regeneration and rooting processes lasted only 5 weeks. The shoot apices of both genotypes developed successfully without intervening callus formation, and no significant differences between cultivars were found. All regenerated plants of both genotypes were phenotypically normal and set seeds. This shoot meristem-based rapid regeneration method can also be used in the cases of biolistic and Agrobacterium-mediated transformation.
Keywords: Gossypium hirsutum; regeneration; organogenesis; shoot apical meristem; rooting; GOSSYPIUM-HIRSUTUM; PLANT-REGENERATION; EXPLANTS